2018
DOI: 10.1063/1.5017784
|View full text |Cite
|
Sign up to set email alerts
|

Structure factors of carbon nanotubes on the thermal conductivity of carbon nanotube/epoxy composites

Abstract: The structure factors of carbon nanotubes such as the dispersion, morphology and size have effects on the thermal conductivity of carbon nanotube/epoxy composites (kc). However, the behavior how these structure factors affect the kc has still not been fully understood. To seek the answer, three-dimensional computational models containing various dispersion of bending single wall carbon nanotubes (SWCNTs) are developed using the finite element method. A conjecture is proposed based on these models that the disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…However, excessive CNTs may cause locally concentrated heat conduction networks due to the agglomeration of CNTs. These networks significantly diminished the efficiency of thermal conduction due to the lack of interconnected channels 40 . Consequently, the curing degree of CFRP laminates in different local regions became disparate, which led to inhomogeneous resistance distribution during the SRE heating process.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, excessive CNTs may cause locally concentrated heat conduction networks due to the agglomeration of CNTs. These networks significantly diminished the efficiency of thermal conduction due to the lack of interconnected channels 40 . Consequently, the curing degree of CFRP laminates in different local regions became disparate, which led to inhomogeneous resistance distribution during the SRE heating process.…”
Section: Resultsmentioning
confidence: 99%
“…It indicates that the addition of CNTs can increase the curing degree of the CFRP laminates, because the CNTs have a catalytic effect on the curing reaction of epoxy resin, leading to a decrease in the active energy of epoxy matrix composites during the curing process, which is a favor to the enhancement of curing degree for epoxy matrix composites 43 . In addition, for SRE heating, the CNTs network in the resin matrix can provide additional electrical and thermal conduction for the preparation of CFRP composites, which is favored to improve the curing degree due to the in‐situ curing mechanism 40,44 . However, the CFRP laminate composites with 1.5 wt% CNTs had the lowest value of T g and curing degree, which indicated that excessive CNTs have a negative effect on the curing degree of CFRP composites fabricated by SRE heating due to nonuniform heating caused by agglomeration of CNTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 shows that the DOSs related to higher temperatures were shifted to higher energies as the bands of energies were expanded with the CNTs. Knowing about the structural properties of CNTs can give us information about the thermal conductivity of these materials [32]. This opens the possibility of overcoming the challenges of interdependency between the structural, mechanical, and optical parameters of CNTs [33].…”
Section: Radial Deformation In Different Temperaturesmentioning
confidence: 99%
“…The other important issue is the high interfacial thermal resistance between nanofiller and polymeric matrix . Previous published studies showed that pristine CNTs at low concentration can enhance TC when a good dispersion is reached. Nonetheless, a beneficial method for improving the epoxy–CNT interactions and thus the dispersion of CNTs is their functionalization (usually by oxidizing the surface), which can preserve the CNT pristine structure, through delocalized π‐bond interactions .…”
Section: Introductionmentioning
confidence: 99%